Mesenchymal stem cell-derived exosomal microRNA-133b suppresses glioma progression via Wnt/β-catenin signaling pathway by targeting EZH2 - Xu, Haiyang; Zhao, Guifang; Zhang, Yu; Jiang, Hong; Wang, Weiyao; Zhao, Donghai; Hong, Jin; Yu, Hongquan; Qi, Ling (Stem cell research & therapy, 2019)
Mesenchymal stem cells (MSCs) play a significant role in cancer initiation and metastasis, sometimes by releasing exosomes that mediate cell communication by delivering microRNAs (miRNAs). This study aimed to investigate the effects of exosomal miR-133b derived from MSCs on glioma cell behaviors. Microarray-based analysis identified the differentially expressed genes (DEGs) in glioma. The expression patterns of EZH2 and miR-133b along with interaction between them were clarified in glioma. The expression of miR-133b and EZH2 in glioma cells was altered to examine their functions on cell activities. Furthermore, glioma cells were co-cultured with MSC-derived exosomes treated with miR-133b mimic or inhibitor, and EZH2-over-expressing vectors or shRNA against EZH2 to characterize their effect on proliferation, invasion, and migration of glioma cells in vitro. In vivo assays were also performed to validate the in vitro findings. miR-133b was downregulated while EZH2 was upregulated in glioma tissues and cells. miR-133b was found to target and negatively regulate EZH2 expression. Moreover, EZH2 silencing resulted in inhibited glioma cell proliferation, invasion, and migration. Additionally, MSC-derived exosomes containing miR-133b repressed glioma cell proliferation, invasion, and migration by inhibiting EZH2 and the Wnt/β-catenin signaling pathway. Furthermore, in vivo experiments confirmed the tumor-suppressive effects of MSC-derived exosomal miR-133b on glioma development. Collectively, the obtained results suggested that MSC-derived exosomes carrying miR-133b could attenuate glioma development via disrupting the Wnt/β-catenin signaling pathway by inhibiting EZH2, which provides a potential treatment biomarker for glioma.